Practices and challenges in the procurement of goods of Bangladesh Railway: a case study on locomotive spare-parts procurement - Islam, Md. Anwarul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.